2021
DOI: 10.1002/cncr.33775
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic risk factors for radiation‐associated ototoxicity: A report from the Childhood Cancer Survivor Study and the St. Jude Lifetime Cohort

Abstract: BACKGROUND Cranial radiation therapy (CRT) is associated with ototoxicity, which manifests as hearing loss and tinnitus. The authors sought to identify clinical determinants and genetic risk factors for ototoxicity among adult survivors of pediatric cancer treated with CRT. METHODS Logistic regression evaluated associations of tinnitus (n = 1991) and hearing loss (n = 2198) with nongenetic risk factors and comorbidities among CRT‐treated survivors in the Childhood Cancer Survivor Study. Genome‐wide association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…A systematic review demonstrated that self-reported hearing loss based on questionnaires could accurately distinguish subjects with hearing difficulty from those without hearing difficulty (Chou et al 2011 ). Previous studies utilizing self-reported hearing status have also successfully identified several genetic variants for radiation-related hearing loss in childhood cancer survivors (Trendowski et al 2021 ), and age-related hearing impairment in UK Biobank populations (Wells et al 2019 ). Therefore, we think hearing evaluation based on subjective sensation may be a feasible and cost-effective measurement for alternative, when audiometry test is absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review demonstrated that self-reported hearing loss based on questionnaires could accurately distinguish subjects with hearing difficulty from those without hearing difficulty (Chou et al 2011 ). Previous studies utilizing self-reported hearing status have also successfully identified several genetic variants for radiation-related hearing loss in childhood cancer survivors (Trendowski et al 2021 ), and age-related hearing impairment in UK Biobank populations (Wells et al 2019 ). Therefore, we think hearing evaluation based on subjective sensation may be a feasible and cost-effective measurement for alternative, when audiometry test is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we examined the correlations of gene expression with radiosensitivity in the cell line types mentioned above (Trendowski et al 2021 ). Radiosensitivity was measured by the surviving fraction after 2 Gy radiation (SF2) from the 9-days viability assay in tumor cell lines (Yard et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PharmacoG x and RadioG x packages resemble each other a lot in their object structure. The PharmacoG x package is used to analyze big pharmacogenomic data sets efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…Given the increased survival in PBTS, there needs to be more efforts to understand and improve the long-term outcomes [28], particularly the risk of neurobehavioral impairments such as emotional, psychosocial, and attention problems. Such information will be useful to ensure that PBTS at risk of neurobehavioral impairment can receive early diagnosis and interventions.…”
Section: Introductionmentioning
confidence: 99%